Features of the Transformation of the Decade of the Lithuanian Media - Ustilaitė, Darija (Žurnalistikos tyrimai, 2023)
World events, the development of information technology and other factors have increased the flow of information and changed the nature of journalists’ work over the last 10 years. However, journalists, despite the transformation and increased opportunities to expand the range of news, can still cover only a certain part of the information. Media workers, due to limited space, time or human resources, select just part of the events that become news. Selected news published in the media influence how society perceives and interprets reality.In this article content analysis and in-depth interviews were used to investigate the transformations that Lithuanian media has undergone over the last 10 years, also the aim was to identify which news media has paid and are paying the most attention to, how and why the specificity of news has changed.
Keywords: transformation; radio stations; online newspapers; television news services; news; journalists